Revision Rhinoplasty: Retrospective Chart Review Analysis of Deformities and Surgical Maneuvers in Patients with Nasal Airway Obstruction—Five Years of Experience - Goudakos, John K.; Daskalakis, Dimitrios; Patel, Kalpesh (Facial Plastic Surgery, 2017)
Nasal airway obstruction is one of the most frequent causes of revision rhinoplasty in patients after previous rhinoplasty procedure. Purpose of this study is to present the deformities and the surgical maneuvers conducted in revision rhinoplasty patients with functional complaint, anatomical sites at risk, and potential prophylactic maneuvers. This study is a retrospective chart review analysis of 46 consecutive revision rhinoplasty procedures in patients with nasal airway obstruction. Inclusion criteria were at least one previous rhinoplasty and nasal airway obstruction as the epicenter of patients' complaint. Thorough clinical examination to certify the obstruction was performed. Deformities noted were separated in three categories according to functional, cosmetic, and combination of functional and cosmetic implications. Surgical maneuvers conducted were reviewed. Deformities found were checked for statistically significant coexistences. The average patient age was 34.9 years. The mean number of previous septorhinoplasties was 1.33. Nasal ventilation obstruction mainly caused either by septum deviation or nasal valve dysfunction was identified in 91.3% of our patients. Surgical maneuvers conducted included placement of grafts in 89.1% of all cases, septoplasty in 76.1%, lateral wall support in 47.8%, and placement of spreader grafts in 39.1% of patients. The average preoperative Nasal Obstruction Symptom Evaluation (NOSE) score was 61 ± 15 and it improved substantially, even from month 1, postoperatively. Owing to high prevalence of nasal airway obstruction after primary or secondary rhinoplasty, we conducted the first retrospective chart review study to identify the most common deformities in revision rhinoplasty patients with nasal airway obstruction and the appropriate surgical maneuvers to address them. Septum deviation and nasal valve dysfunction were the two pillars of nasal airway obstruction in those patients.
Keywords: nasal airway obstruction; revision rhinoplasty; functional complaint